Clinical data, limitations and perspectives on chimeric antigen receptor T-cell therapy in multiple myeloma - Beauvais, David; Danhof, Sophia; Hayden, Patrick J.; Einsele, Hermann; Yakoub-Agha, Ibrahim (Current Opinion in Oncology, 2020)
Purpose of review Despite considerable therapeutic advances over the last decade, multiple myeloma remains an incurable disease. Novel treatment strategies are urgently needed. T cells can be genetically modified to express chimeric antigen receptors (CARs) targeting defined surface antigens on tumor cells. To date, over 90 clinical trials investigating the use of CAR T cells in multiple myeloma have been registered. Recent findings Although two CD19-directed CAR T-cell products have been approved, CD19 surface expression on plasma cells is limited or absent and CAR T-cell therapy in multiple myeloma is less advanced. B-cell maturation antigen (BCMA)-directed CAR T cells have shown promising efficacy and safety profiles in various phase I/II clinical trials. However, almost all treated patients continue to relapse. The current focus is therefore on strategies to overcome resistance mechanisms. These include the targeting of other surface antigens, refinements in T-cell signaling and dual-targeting approaches. Summary CAR T-cell therapy has finally moved into routine clinical use, the first experiments having taken place over 30 years ago. A BCMA-directed product for the treatment of multiple myeloma is expected to be approved shortly. However, further refinements of both CAR T-cell constructs and treatment protocols will be required to boost persistence, overcome resistance and reduce toxicities.
CRIS-Team Scopus Importer:2023-03-23
Keywords: B-cell maturation antigen; CD19; Chimeric antigen receptor T-cell; Multiple myeloma